Productivity and Economics of Different Double Cropping Systems at Farmer's Field in Tikamgarh District of Madhya Pradesh - P. K. Tyagi and V. K. Singh, (Indian Journal of Extension Education, 2017)
The present study was conducted to assess the productivity and economics of different cropping systems at Farmer's Fieldin five blocks of Tikamgarh district of Madhya Pradesh. The pooled data revealed that the total productivity in terms ofseed yield (45.0 q/ha) as well as wheat equivalent yield (54.1 q/ha) was recorded the highest in soybean-wheat system.Similarly, the production efficiency (19.3 kg/ha/day) and net monetary return (` 36882/ha) were also recorded the highestin soybean-wheat system. However, net monetary return per day was recorded the maximum in blackgram-coriandersystem (` 160/ha/day) closely followed by soybean-wheat (` 158/ha/day) system. Soybean-wheat system gave anadvantage of a net return of ` 10467, ` 8007 and ` 1310 per hectare over sesame-wheat, blackgram-mustard andblackgram-coriander systems respectively. Similarly, increase in net monetary return from blackgram-coriander oversesame-wheat was ` 9157/ha and over blackgram-mustard was ` 6697/ha. The net return per rupee invested (B:C) wasrecorded the highest in blackgram-coriander (1.92) and the lowest in sesame-wheat (1.07) system. It was evident from theresults that soybean-wheat system exhibited superiority over other cropping systems in Tikamgarh district. Similarly,growing the coriander crop after blackgram was more remunerative than growing mustard crop. Blackgram-coriandersystem was also profitable over sesame-wheat system.